Plutarhovi napotki za srečen zakon - Sunčič, Maja (Monitor ISH, 2004)
Plutarch's advice for a happy marriage. The paper analyses Plutarch's Advice to the Bride and Groom (Coniugalia praecepta), written as a wedding gift to the author's former students. Plutarch presents his fantasy of the ideal marriage with the help of colourful analogies and didactic counsels. One of the most important aspects of his treatise is the presentation of an idealised and phantasmic wife, a collage of the past and the author's present. Since the idealised wife plays the key role in developing a happy philosophical marriage, the greater part of the advice is addressed to the bride.
Keywords: antika; classical antiquity; marriage; zakonska zveza; ženske; woman; družbeni položaj; zakonska ljubezen; idealna ženska